PENGARUH PENDIDIKAN, PERSON JOB FIT DAN PUNISHMENT TERHADAP KINERJA PEGAWAI KANTOR DINAS PENDIDIKAN PROVINSI JAWA TIMUR - Priyo Budiarto; Ika Novaliana; Indrian Supheni (Gapenas Publisher, 2023)
The research sample was 98 respondents taken from employees of the East Java Provincial Education Office. The results of the research concluded that there is a significant effect of education on employee performance, there is a significant effect of person job fit on employee performance, there is a significant effect of punishment on employee performance and there is a joint effect of education, person job fit and punishment on the performance of Education Department employees East Java Province. Education, person job fit and punishment which have a significant influence mean that the East Java Province DINDIK must always update the curriculum vitae and academic achievements of employees and non-academic employees. The results of the research show that there are other factors that can influence employee performance besides education, person job fit and punishment, therefore it is recommended that the personnel section of the East Java Provincial Education Office should pay more attention to qualification levels such as providing wages, learning or training, incentives for improvement. career advancement according to the basic abilities of employees and increasing employee work motivation